Human Leukocyte Antigen (HLA) 2019
DOI: 10.5772/intechopen.81645
|View full text |Cite
|
Sign up to set email alerts
|

HLA Allele Frequencies in Pediatric and Adolescent Multiple Sclerosis Patients

Abstract: Early-onset (pediatric and adolescent) multiple sclerosis (MS) is a chronic autoimmune and neurodegenerative disorder of the central nervous system, which accounts for 3-5% of all MS cases. The major histocompatibility complex (MHC) with its polymorphisms has been the genetic locus with the most robust association with adult MS, since its first discovery in the 1970s. Nowadays, human leukocyte antigen (HLA) typing studies and genome-wide association studies (GWAS) have tried to provide insight into the genetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 60 publications
0
1
0
Order By: Relevance
“…The involvement of antigen presentation, in recovery mechanism is not surprising, since these processes are known to play a role in MS disease course and in MS susceptibility presented by polymorphism of HLA‐DQB1, 29‐31 IL4R, 32 and HSP970 33,34 genes. A review by Anagnostouli et al (2018) 35 concluded that while HLA‐DRB1*1501 is clearly a risk factor for both POMS and AOMS patients, the results regarding the association between HLA‐DRB1 variability and age of MS onset are conflicting: some studies describe HLA‐DRB1*1501 as being associated with an earlier onset age, whereas others claim that there is no correlation between HLA‐DRB1*1501 and age. Of note, the HLA‐DRB1*1501 allele, which is known to increase the risk for developing MS 36,37 , is associated with a high expression level of HLA‐DQB1 38 .…”
Section: Discussionmentioning
confidence: 99%
“…The involvement of antigen presentation, in recovery mechanism is not surprising, since these processes are known to play a role in MS disease course and in MS susceptibility presented by polymorphism of HLA‐DQB1, 29‐31 IL4R, 32 and HSP970 33,34 genes. A review by Anagnostouli et al (2018) 35 concluded that while HLA‐DRB1*1501 is clearly a risk factor for both POMS and AOMS patients, the results regarding the association between HLA‐DRB1 variability and age of MS onset are conflicting: some studies describe HLA‐DRB1*1501 as being associated with an earlier onset age, whereas others claim that there is no correlation between HLA‐DRB1*1501 and age. Of note, the HLA‐DRB1*1501 allele, which is known to increase the risk for developing MS 36,37 , is associated with a high expression level of HLA‐DQB1 38 .…”
Section: Discussionmentioning
confidence: 99%